Діагностика загроз безпеці праці на будівельних підприємствах - Андрієнко, В. М. (Ways to Improve Construction Efficiency, 2013)
In the article the diagnosis threats safety on construction enterprises in Ukraine. Identified internal security threats labor on construction enterprises in Ukraine. The basic factors that lead to injuries in construction. Identified external threats labor on construction enterprises in Ukraine.